A 10- and 15-year performance analysis of ESC/EAS and ACC/AHA cardiovascular risk scores in a Southern European cohort - Cátia Santos-Ferreira; Rui Baptista; Manuel Oliveira-Santos; José Pereira Moura; Lino Gonçalves (BMC Cardiovascular Disorders, 2020)
Abstract Background A key strategy for the primary prevention of cardiovascular disease (CVD) is the use of risk prediction algorithms. We aimed to investigate the predictive ability of SCORE (Systematic COronary Risk Estimation) and PCE (Pooled Cohort Equations) systems for atherosclerotic CVD (ASCVD) risk in Portugal, a low CVD risk country, at the 10-year landmark and at a longer, 15-year follow-up. Methods The SCORE and PCE 10-year risk estimates were calculated for 455 and 448 patients, respectively. Discrimination was assessed by Harrell’s C-statistic. Calibration was analyzed by standardized incidence ratios (SIR). Results During the 10-year follow-up, 7 fatal ASCVD events (the SCORE outcome) and 32 any ASCVD events (the PCE outcome) occurred. The SCORE system showed good discrimination (C-statistic 0.83), while the PCE showed poor discrimination (C-statistic 0.62). Calibration was similar for both systems, according to SIR: SCORE, 0.3 (95% CI 0.1–0.7); PCE, 0.5 (95% CI 0.4–0.7). Globally, both 10-year fatal ASCVD risk and any ASCVD risk were overestimated in the overall population and men. However, the risk was underestimated by both systems in women. Despite an overestimation of 15-year fatal ASCVD by SCORE, the 15-year any ASCVD observed incidence was 1.8 times the 10-year incidence among men and 1.4 times among women. This acceleration of CVD risk was more relevant in the lowest classes of ASCVD risk. Conclusion In this prospective, contemporary, Portuguese cohort, the SCORE had better discriminatory power and similar calibration compared to PCE. However, both risk scores underestimated 10-year ASCVD risk in women.